1999
DOI: 10.1890/1051-0761(1999)009[1160:eovocf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Volatile Organic Compounds From Ozone-Exposed Plants

Abstract: Plants produce a number of volatile organic compounds (VOCs), and this release plays a significant role in atmospheric chemistry. Although certain factors controlling the emission rates of VOCs from plants are reasonably well understood, the influence of abiotic stress, such as elevated ozone concentrations, is unknown. Therefore, the emission of VOCs from tobacco plants (Nicotiana tabacum L. cv. Bel B and Bel W3) and Scots pine (Pinus sylvestris L.) were studied in continuously stirred tank reactors under ozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 32 publications
(26 reference statements)
3
103
0
Order By: Relevance
“…A variety of factors, such as pathogen attack, exposure to UV light, herbivory, wounding and exposure to elicitor molecules can induce hypersensitive cell death [Doke et al, 1994], and thus could lead to an enhanced volatilization of BCAR from storage pools. Some of these factors, e.g., herbivory [Kessler and Baldwin, 2001;Turlings et al, 1998;Rodriguez-Saona et al, 2001], ozone exposure [Heiden et al, 1999] and the treatment with the elicitor methyl jasmonate [Rodriguez-Saona et al, 2001] have been found to induce the emission of BCAR and/or other sesquiterpenes from leaves on a timescale of hours or days. Anyway, the increased emission could be attributed to both cell lesions and induced sesquiterpene synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of factors, such as pathogen attack, exposure to UV light, herbivory, wounding and exposure to elicitor molecules can induce hypersensitive cell death [Doke et al, 1994], and thus could lead to an enhanced volatilization of BCAR from storage pools. Some of these factors, e.g., herbivory [Kessler and Baldwin, 2001;Turlings et al, 1998;Rodriguez-Saona et al, 2001], ozone exposure [Heiden et al, 1999] and the treatment with the elicitor methyl jasmonate [Rodriguez-Saona et al, 2001] have been found to induce the emission of BCAR and/or other sesquiterpenes from leaves on a timescale of hours or days. Anyway, the increased emission could be attributed to both cell lesions and induced sesquiterpene synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves of several deciduous forest trees (Betula pendula, B. pubescens, Populus tremula and Sambucus nigra [Zhang et al, 1999]; Carpinus betulus [König et al, 1995]) emit considerable amounts of this reactive volatile hydrocarbon. Moreover, BCAR has been reported to be one of the main components of constitutive or induced terpenoid emissions from foliage of a variety of agricultural plant species, e.g., Prunus avium, Vitis vinifera, Olea europea, Prunus persica [Arey et al, 1991], Citrus sinensis [Hansen and Seufert, 1999], potato plants [Agelopoulos et al, 2000], and leaves of tobacco [Heiden et al, 1999], sunflower [Schuh et al, 1997], maize [Turlings et al, 1998] and cotton [Rodriguez-Saona et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone-resistant and susceptible tobacco (Nicotiana tabacum) plants have different temporal patterns of VOC (sesquiterpene) production in response to exposure to ozone. Ozone-resistant tobacco produces sesquiterpenes immediately after exposure while ozone-susceptible tobacco does not (Heiden et al, 1999). Work with A. thaliana suggests a relationship between ozone resistance and the production of VOCs that quench ozone (Holopainen, 2004;Dudareva et al, 2006).…”
Section: Tansley Reviewmentioning
confidence: 99%
“…Recent work provides evidence that VOC may be involved in protection against oxidizing agents like ozone (Zeidler et al, 1997;Loreto et al, 2001;Penuelas & Llusia, 2001). The influence of elevated atmospheric ozone on the emission capacity of plants, as an abiotic stress factor, is currently under debate (Kimmerer & Kozlowski, 1982;Heiden et al, 1999Heiden et al, , 2003Llusia et al, 2002;Wildt et al, 2003), and it seems that ozone Fig. 7 Seasonal differences of standard emission factors (normalized to 1000 mmol m À2 s À1 of PAR and 30 1C leaf temperature) of monoterpene emission from A. tibourbou and isoprene emission from H. courbaril (panel b), in conjunction with data of ambient temperature and photosynthetic active radiation (PAR) in the days proceeding the measurements (panel a).…”
Section: Intra-specific Seasonal Variation In Voc Emissionmentioning
confidence: 99%